A modified approach for simulating complex compound structures within early design steps - Gruber, Georg; Klein, Daniel; Wartzack, Sandro (8th European LS-DYNA Users Conference, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.amodif_7

An optimized material representation for crashworthy lightweight structures within early design steps - Gruber, Georg; Wartzack, Sandro (Proceedings of the 16th International Conference on Industrial Engineering - Theory, Applications and Practice, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.anopti

A visualization methodology for evaluating parts made of short fiber reinforced thermoplastics regarding their lightweight potential - Gruber, Georg; Wartzack, Sandro; Kößler, Johannes (Proceedings of the 19th International Conference on Engineering Design, 2013)
Injection molded, short fiber reinforced thermoplastics are a promising lightweight material. However, the component design is getting complex with this type of material due to the process induced fiber orientation. To achieve substantial progress in lightweight design, the resulting anisotropic material properties have to be taken advantage of effectively. The most important correcting variables influencing the fiber orientation are the part's geometry and the gate design (position and type of gates). The goal of the present paper is introducing a new evaluation method, supporting the product developer at detecting the most appropriate geometry and gate layout. The basic idea behind the new approach is examining the deviations between the load path and the fiber orientation pattern. With the help of new quality criteria it can be rated to which extent load path and fiber orientation are in harmony. The methodology is implemented as a software tool, delivering a mean quality criterion per part as well as a contour plot enabling also the analysis of the local distribution of the focused quality criterion. The potential of the new approach is demonstrated within a brief case study.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.avisua
Keywords: Decision making; Lightweight design; Short fiber reinforced thermoplastics; Simulation; Visualization

Concept for the Architecture of A Self-Learning Engineering Assistance System - Röhner, Sebastian; Gruber, Georg (Proceedings of Norddesign 2010: International Conference on Methods and Tools for Product and Production development, 2010)
Considerable efforts have been taken in the past decades to integrate design and manufacturing knowledge into the product development process. A common approach is to offer designers the support of knowledge based systems, expert systems or assistance systems. There are several methodologies of these systems which differ in representing and reasoning of knowledge. Keeping their knowledge base up to date is a crucial, yet demanding issue. Currently most means of knowledge acquisition are labour-intensive for knowledge engineers and domain experts. Thus, the knowledge acquisition process is often the bottleneck, and automatic knowledge acquisition from databases is a promising approach to overcome it. In this paper a concept for the architecture of a self-learning engineering assistance system is presented, that uses data mining methods for the acquisition, updating and reasoning of knowledge.
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.concep
Keywords: Artificial intelligence; Assistance system; Data mining

Consideration of anisotropic material properties in mechanical design within early design phases - Gruber, Georg; Klein, Daniel; Ziegler, Philipp; Wartzack, Sandro (NordDesign 2012 - Proceedings of the 9th NordDesign Conference, 2012)
To achieve the goal of simulating the structural behavior of parts made of short fiber reinforced polymers with satisfactory accuracy and justifiable modeling effort, a new approach adapted to the needs of the early design steps was developed at the Chair of Engineering Design (KTmfk). Hereby, the various effects of material behavior are modeled by overlapping two different material models in one finite element definition. The anisotropic material properties are determined by an injection molding simulation. The complexity of the resulting fiber distribution is reduced to just three values per finite element. The paper's focus is the introduction of an automated method supporting the determination of the numerical material parameter and a new tensor based method enabling the averaging of the complex orientation state. The benefits of the new methods and a validation are presented.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Early design steps; Fiber reinforced polymers; Lightweight design; Simulation

Consideration of Anisotropic Material Properties in Mechanical Design within Early Design Steps - Gruber, Georg; Klein, Daniel; Ziegler, Philipp; Wartzack, Sandro (Proceedings of the 9th Norddesign, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.consid_2

Consideration of Orientation Properties of Short Fiber Reinforced Polymers within Early Design Steps - Gruber, Georg; Haimerl, Andreas; Wartzack, Sandro (12th International LS-DYNA® Users Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.consid

Crashgerechter Leichtbau - Wartzack, Sandro; Gruber, Georg (Konstruktion, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.crashg

Crashsimulation kurzfaserverstärkter Kunststoffbauteile - Ein Ansatz für frühe Entwicklungsphasen - Gruber, Georg; Wartzack, Sandro (Kunststoffe + SIMULATION, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.crashs

Die Crux der Faserorientierung - Klein, Daniel; Gruber, Georg; Wartzack, Sandro (Kunststoffe, 2014)
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.diecru
Keywords: Leichtbau; Composites; kurzfaserverstärkte Thermoplaste

Evaluierung der orientierungsbezogenen Leichtbaugüte - Gruber, Georg; Wartzack, Sandro (Konstruktion, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.evalui_2

Evaluierung Integrativer Simulationsansätze zur Prognose des Strukturverhaltens kurzfaserverstärkter Kunststoffproben - Gruber, Georg; Wartzack, Sandro (6. Landshuter Leichtbau-Colloquium, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.evalui

Komplexitätsreduzierte integrative Struktursimulation kurzfaserverstärkter Kunststoffbauteile mit LS-Dyna - Gruber, Georg; Liebst, Fabian; Wartzack, Sandro (ANSYS Conference & 32th CADFEM Users' Meeting., 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.komple

Materialparameter-Optimierung für die Crashberechnung in frühen Entwicklungsphasen - Gruber, Georg; Klein, Daniel; Wartzack, Sandro (NAFEMS 2012, 2012)
Durch die drastische Verknappung der Ressourcen und den damit verbundenen Restriktionen seitens der Politik (z.B. CO2-Grenzwerte) hat speziell in der Automobilindustrie der Leichtbau enorm an Bedeutung gewonnen. Um Leichtbaustrategien möglichst effizient durchführen zu können, ist es erforderlich bereits die frühe Entwicklungsphase auszunutzen, da hier noch die maximale Designfreiheit zur Berücksichtigung aller Anforderungen vorliegt. Doch gerade die Berechnung und Auslegung in Bezug auf die Crashsicherheit von Bauteilen aus Verbundwerkstoffen ist aufgrund der komplexen mechanischen Eigenschaften und der fertigungsbedingten Anisotropie bisher noch sehr schwierig und zeitaufwändig. Deshalb wurde ein Ansatz entwickelt, der es ermöglicht eine Materialbeschreibung für die Crashberechnung in frühen Entwicklungsphasen zu generieren. Über die Funktion *PART_COMPOSITE werden in LS-DYNA® für ein einziges Bauteil mehrere bereits bestehende Materialmodelle definiert. Dabei enthalten diese Materialmodelle Parameter, die so aufeinander abgestimmt werden können, dass sich in Summe das gewünschte Materialverhalten einstellen lässt. Die Identifikation dieser Materialparameter wird durch den Einsatz der Optimierungssoftware LS-OPT® entscheidend beschleunigt. Damit kann innerhalb kürzester Zeit ein valides Materialmodell erzeugt werden, das den Anforderungen in frühen Entwicklungsphasen gerecht wird. Das genaue Vorgehen wird im Folgenden am Beispiel eines kurzfaserverstärkten Thermoplasten gezeigt.
Keywords: Simlution; Crash; Composites

Methodische Unterstützungsansätze für die Entwicklung additiv gefertigter Bauteile - Gruber, Georg; Kestel, Philipp; Staab, Andreas; Wartzack, Sandro (Tagungsband der Rapid.Tech 2013 - Fachmesse und Anwendertagung für Rapid-Technologie, 2013)
Additive manufacturing allows the creation of individual and highly innovative products. The reasons are high geometric flexibility and the possibility of including additional functions in the part offered by additive manufacturing. However, the complex dependencies between manufacturing parameters and the resulting properties of the parts are challenging. The present paper deals with special characteristics of additive manufacturing regarding form design and feasibility. Furthermore, state of the art approaches assisting the product developer at the design process are discussed. The focus of the paper is the introduction of a concept of a new process chain, supporting the design process of additive manufactured parts. The goal of the new development process is generating the part’s geometry directly by numerical optimization methods like topology optimization. This is possible thanks to the geometric flexibility offered by additive manufacturing. To be able to consider graded and anisotropic material properties within the optimized structure, an enhanced form of optimization – the so called free material optimization – shall be deployed. The distinct setup of the process chain as well as customized pre and post processing tools allow for a development process which does not involve CAD tools being used to generate the parts geometry.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.method

Simulation based generation of an initial design taking into account geometric deviations and deformations - Walter, Michael; Breitsprecher, Thilo; Gruber, Georg; Wartzack, Sandro (Proceedings of the 18th International Conference on Engineering Design 2011 (ICED11), 2011)
The success of a product's development is essentially affected by its functionality. So the product developer has to ensure the functionality as early as possible. Since this usually can't be achieved with the first design several iterations are needed to modify the design. The product's functionality depends largely on the interaction of its components and their geometries. So geometric deviations of these components need to be taken into account. These deviations can result e.g. from manufacturing discrepancies or being operation-depending like deformations. This paper presents an approach which enables the product developer to determine an initial design proposal that fulfils its function. So no time- and money-consuming iterations are needed. Therefore the approach uses methods and tools like tolerance allocation, topology optimization and parameter optimization at an early stage. The tolerance allocation is needed to define the functional requirement of the non-ideal components. The optimization tools are used to create the initial design proposal fulfilling the functional requirement. A case study of a non-ideal scissor-type lift table illustrates the approach.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.simula
Keywords: Early functional validation; Initial design proposal; Non-ideal parts; Topology optimization

Simulative Parameterstudien an Wellblech-Sandwichstrukturen - Gruber, Georg; Wartzack, Sandro (ANSYS Conference & 29th CADFEM Users' Meeting, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.simula_6

Verbesserungspotentiale in der Entwicklung und Validierung hoch dynamisch belasteter Leichtbaukomponenten im Umfeld der Zulieferindustrie - Gruber, Georg; Walter, Michael; Wartzack, Sandro (Design for X. Beiträge zum 21. DfX-Symposium, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.verbes

Vergleichende Studie der Topologie-Optimierungsalgorithmen CONLIN und SUMT - Gruber, Georg; Stockinger, Andreas; Tremmel, Stephan; Wartzack, Sandro (Tagungsband zum 5. Landshuter Leichtbau-Colloquium, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.vergle